PENERAPAN MODEL PEMBELAJARAN KOOPERATIF PENDEKATAN STRUKTURAL NUMBERED HEADS TOGETHER (NHT) UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS VII.5 SMP NEGERI 17 PEKANBARU - Putri Ayu Lestari; Rini Dian Anggraini; Yenita Roza (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract : This classroom action research is aimed to improve learning process and mathematics learning outcomes by implementing Cooperative Learning Model with Structural Numbered Heads Together (NHT) Approach. The research subjects are 36 heterogenous academic ability level students of the VII.5 class of Junior High School 17 Pekanbaru in academic year of 2016/2017. The research implemented in two cycles in which each cycle consisted of four phases, i.e; namely planning, implementing, observing, and reflecting. By the end of a cycle, formative test was held. The data was collected by doing observation of teachers and students activities and formative test. The research shows learning process improvement after the implementation Cooperative Learning Model with Structural Numbered Heads Together (NHT) approach.. Most of the students participated actively and responsible in the learning process e.g. discussing, presenting student’s worksheet, responding to classmate’s presentation, and drawing the lesson conclusion. Additionally, the students afforded to answer the written test given by teacher well. Furthermore, the number of students passing the KKM on base score, formative test I (first cycle), formative test II (second cycle) were respectively 36,1%, 50%, and 69,4%. The percentage of KKM achievement also indicates the increase after the implementation, thus it can be said that the students’ learning outcomes also increase. Finally, the research also shows that cooperative learning model with structural Numbered Heads Together (NHT) approach can improve mathematics learning process and learning outcomes of VII.5 class students of Junior High School 17 Pekanbaru. Key Words : Math Learning Outcomes, Cooperative Learning Model with Structural Numbered Heads Together (NHT) Approach, Classroom Action Research.